2018
DOI: 10.1021/acs.langmuir.8b01366
|View full text |Cite
|
Sign up to set email alerts
|

Emergent Properties of Antiagglomerant Films Control Methane Transport: Implications for Hydrate Management

Abstract: The relationship between collective properties and performance of antiagglomerants (AAs) used in hydrate management is handled using molecular dynamics simulations and enhanced sampling techniques. A thin film of AAs adsorbed at the interface between one flat sII methane hydrate substrate and a fluid hydrocarbon mixture containing methane and n-dodecane is studied. The AA considered is a surface-active compound with a complex hydrophilic head that contains both amide and tertiary ammonium cation groups and hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 32 publications
(60 citation statements)
references
References 133 publications
(295 reference statements)
3
57
0
Order By: Relevance
“…To quantify synergistic or antagonistic effects, we monitored changes in the structure of the AAs within the interfacial film due to the presence of aromatics. It should be noted that the order of the interfacial film was found to be correlated with the AAs performance, as well as with the ability of methane to diffuse from the hydrocarbon phase to the hydrate substrate in our prior studies 8,27 . To quantify the order of the AAs films, we calculated the deuterium order parameter, S CD , for carbon atoms in the long alkyl tails of the AAs.…”
Section: Number Of N-dodecane Moleculesmentioning
confidence: 59%
See 2 more Smart Citations
“…To quantify synergistic or antagonistic effects, we monitored changes in the structure of the AAs within the interfacial film due to the presence of aromatics. It should be noted that the order of the interfacial film was found to be correlated with the AAs performance, as well as with the ability of methane to diffuse from the hydrocarbon phase to the hydrate substrate in our prior studies 8,27 . To quantify the order of the AAs films, we calculated the deuterium order parameter, S CD , for carbon atoms in the long alkyl tails of the AAs.…”
Section: Number Of N-dodecane Moleculesmentioning
confidence: 59%
“…1a. To construct the initial configurations, we followed the procedure described in our previous study 27 . Each simulated system contains a sII methane hydrate substrate of size 5.193 × 5.193 × 3.462 nm.…”
Section: Simulation Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…184 Some hydrocarbon chains were found to penetrate the AAs film, in qualitative agreement with experimental data by Tokiwa et al 185 These results also provide a new hypothesis for the mechanism by which AAs function: when the AAs form an ordered film, they could prevent methane transport across the interface. 186…”
Section: Some Advancements In the Understanding Of Clathrate Hydratesmentioning
confidence: 99%
“…Because the density of methane within such interfacial films was negligible, Bui et al [47] suggested that the AAs they considered could prevent hydrate plug formation, in part, causing an interfacial barrier that prevent both water and methane from reaching the hydrate particle. Sicard et al [48] quantified the strong free energy barrier encountered by methane when it travels across such interfaces. For these calculations, enhanced sampling techniques including metadynamics, umbrella sampling, and adiabatic biased MD were implemented.…”
Section: Recent Simulationsmentioning
confidence: 99%